Mitral Subvalvular Aneurysm in a Patient with Chagas Disease and Recurrent Episodes of Ventricular Tachycardia - Tereza Augusta Grillo; Guilherme Rafael S. Athayde; Ana Flávia L. Belfort; Reynaldo C. Miranda; Andrea Z. Beaton; Bruno R. Nascimento (Case Reports in Cardiology)
Subvalvular left ventricular aneurysm is a rare disease of obscure origin suggesting unique causes such as congenital, traumatic, and inflammatory or infectious diseases. Its mortality is closely related to heart failure, mitral insufficiency, thromboembolic phenomena, and cardiac arrhythmias. Although association with coronary artery disease is not described, the compression of epicardial vessels by the aneurysm may lead to ischemic manifestations. We report here a case of mitral subvalvular left ventricular aneurysm of probable chagasic origin, in a patient with normal left ventricular function evolving with repeated episodes of monomorphic ventricular tachycardia, despite noninducible electrophysiological testing and the use of optimal medical treatment, including amiodarone. The indication for implantable cardioverter-defibrillator in patients with Chagas cardiomyopathy and segmental wall motion abnormalities but without global systolic dysfunction remains unclear in literature, even in the presence of complex ventricular arrhythmias. A brief review of the literature on morphological features, diagnosis, prognosis, and treatment will be also discussed.